2022
DOI: 10.1111/jace.18488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size and shape on the rate of hydrogen produced by Al‐doped SrTiO3 photocatalysts

Abstract: Photocatalytic hydrogen production rates have been measured from Al‐doped SrTiO3 with a range of controlled shapes and sizes using a high‐throughput parallelized and automated photochemical reactor. It is found that the photocatalytic reactivity is influenced by crystal shape and that crystals with a {1 1 0} to {1 0 0} surface area ratio between 1.3 and 1.8 yield more H2 than crystals with other ratios. Crystals with a {1 1 0}/{1 0 0} surface area ratio of 1.8 generate hydrogen at 550 μmol h−1 g−1 at pH 7, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…The obtained O-Vacancy formation energy using the vacancy formation equation was 5.2 eV (where STO formation energy is 6.7 eV), according to the previous literature suggesting a higher concentration of O-vacancies [43,44]. The images before and after optimization with the bond lengths have been displayed in the supplementary information (Fig.SI (20)(21)(22)(23)(24)(25)(26).…”
Section: R×asupporting
confidence: 59%
See 1 more Smart Citation
“…The obtained O-Vacancy formation energy using the vacancy formation equation was 5.2 eV (where STO formation energy is 6.7 eV), according to the previous literature suggesting a higher concentration of O-vacancies [43,44]. The images before and after optimization with the bond lengths have been displayed in the supplementary information (Fig.SI (20)(21)(22)(23)(24)(25)(26).…”
Section: R×asupporting
confidence: 59%
“…It has been used widely for solar cells, batteries, photocatalysis, and fuel cell applications due to its enormously enriched electrical, physical, and optical properties [20]. Also, doping different elements, especially the lower valent such as the Al +3 , La, Nb, Fe, etc., into SrTiO 3 remains a practical approach to enhance the performance by producing abundant O-vacancies of different devices, including photocatalysis and fuel cell [21][22][23][24][25]. Also, in recent years the heterostructure technique has emerged as an exciting area in boosting the performance of fuel cells [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] Both s‐SrTiO 3 and ix‐SrTiO 3 produce hydrogen at a higher rate at pH 7 than that at pH 2 and 12, which is consistent with our previous work reported for undoped SrTiO 3 single crystals [ 24 ] and Al‐doped SrTiO 3 particles. [ 20 ] This is because the amount of surface charge influences band bending, and pH 7 corresponds to a surface charge where neither the photocathodic nor the photoanodic reaction limit the overall reaction rate. For ix‐SrTiO 3 , the rate is higher in pH 7 water than that in 10% methanol solutions, indicating that the anodic half reaction is no longer the rate‐limiting reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It has more recently been reported that when SrTiO 3 particles with controlled shapes are heated in molten SrCl 2 , the shapes are preserved. [ 20 ] This suggests that, while some particle erosion or coarsening is possible, the particles do not completely dissolve and recrystallize.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the smaller the size of the catalyst nanoparticles, the higher the photocatalytic activity. Cerruto et al systematically correlated the photocatalytic activity to the average sizes and size distributions of TiO 2 nanocrystals [ 41 ], while more recently, the study was extended to the hydrogen produced by Al-doped SrTiO 3 photocatalysts [ 42 ] to the visible photocatalytic activity in β-Bi 2 O 3 [ 42 , 43 ], and the reduction of CO 2 in Cu/Cu 2 O nanocrystals [ 44 ]. The surface properties significantly influence the efficiency of the catalyst because, during the photocatalytic process, oxidation and reduction reactions take place on the surface of the catalyst [ 45 , 46 ].…”
Section: Basic Principles Of Photocatalysismentioning
confidence: 99%